Children, poverty and the sustainable development goals - Dornan, P (Wiley, 2017)
The Sustainable Development Goals (SDGs) came into force in January 2016, taking over from the Millennium Development Goals (MDGs). Significant human development progress has occurred in recent decades. Nevertheless, the MDGs have been criticised not least for failing to prioritise inequality and gains for the poorest people. The SDGs create a much more comprehensive agenda and support many key child rights concerns. While SDGs reflect an important global consensus, their delivery depends upon national action.